PTH-070 Patients receiving anti-tnf agents for inflammatory bowel disease: exposure to diagnostic ionising radiation and trends in imaging modalities. (22nd June 2015) - Meredith, S; Dibb, M; Ellis, T; Gordon, M; Probert, C; Subramanian, S; Collins, P
Abstract : Introduction: Concern has been raised as to the risk of malignancy in patients with inflammatory bowel disease related to their exposure to ionising radiation from diagnostic tests. A meta-analysis has reported that 8.8% of patients with inflammatory bowel disease were exposed to potentially harmful levels of diagnostic medical radiation (DMR) (defined as greater than 50 milli-sieverts (mSv)). 1 Patients requiring anti-TNF treatment for management of their disease may be at greatest risk of exposure to diagnostic medical radiation by virtue of their disease activity. AIM: To determine the prevalence of exposure to a potentially harmful dose of DMR in patients receiving anti-TNF treatment and to determine predictors of high exposure. Method: A retrospective review of patients receiving anti-TNF agents for IBD in a tertiary referral centre between 2005 and 2012 was undertaken. Logistic regression was used to identify predictors of exposure to a potentially harmful cumulative effective dose (CED) of >50 mSv in patients with Crohn's disease. Variables considered as potential predictors of a harmful CED included elements of the Montreal classification of disease (site and behaviour of disease and presence of perianal disease), age and sex. Results: A cohort of 149 patients was identified. The median age was 36 (range 18 to 72 years). 135 patients had Crohn's disease. 1137 diagnostic procedures associated with exposure to ionising radiation were performed. The median CED was 10.72mSv (Range 0 to 146). 12% of all IBD patients received a potentially harmful CED of >50 mSv. In patients with Crohn's disease, 9.6% received a CED of > 50mSv. Logistic regression failed to demonstrate a significant association between a CED of > 50mSv and the variables assessed. Abdominal CT scans accounted for 69% of the CED. During the study period the ratio of abdominal MR scans to abdominal CT scans was 1:24 and 2:3 in the first and last quartile of the study period, respectively. Conclusion: 12% of IBD patients receiving anti-TNF agents for IBD in a tertiary setting received a potentially harmful dose of ionising radiation from diagnostic imaging. This was largely related to abdominal CT scans. The temporal trend towards a greater use of non-ionising radiation for diagnostic imaging in this group is therefore reassuring. Disclosure of interest: None Declared. Reference: Chatu et al . Aliment Pharmacol Ther. 2012;35:529